2020
DOI: 10.1124/dmd.119.090324
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Distribution, Metabolism, and Excretion of Capmatinib (INC280) in Healthy Male Volunteers and In Vitro Aldehyde Oxidase Phenotyping of the Major Metabolite

Abstract: Capmatinib (INC280), a highly selective and potent inhibitor of the MET receptor tyrosine kinase, has demonstrated clinically meaningful efficacy and a manageable safety profile in patients with advanced non-small-cell lung cancer harboring MET exon 14-skipping mutations. We investigated the absorption, distribution, metabolism, and excretion of capmatinib in six healthy male volunteers after a single peroral dose of 600 mg 14 C-labeled capmatinib. The mass balance, blood and plasma radioactivity, and plasma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…For example, both SGX523 and JNJ-38877605 (Lolkema et al, 2015) were responsible for nephrotoxicity due to the formation of insoluble metabolites mediated by AOX in human kidney and ultimately leading to discontinuation as a clinical candidate. Capmatinib, a highly selective and potent MET (tyrosine kinase receptor) inhibitor also failed due to high interspecies differences in its AOX mediated metabolism and toxicity (Lolkema et al, 2015;Glaenzel et al, 2020). Considering the implications of interspecies differences in drug development, here we provided a quantitative comparison of non-CYP enzymes in humans versus the non-human primates (cynomolgus and rhesus), dog, rat, and mouse.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both SGX523 and JNJ-38877605 (Lolkema et al, 2015) were responsible for nephrotoxicity due to the formation of insoluble metabolites mediated by AOX in human kidney and ultimately leading to discontinuation as a clinical candidate. Capmatinib, a highly selective and potent MET (tyrosine kinase receptor) inhibitor also failed due to high interspecies differences in its AOX mediated metabolism and toxicity (Lolkema et al, 2015;Glaenzel et al, 2020). Considering the implications of interspecies differences in drug development, here we provided a quantitative comparison of non-CYP enzymes in humans versus the non-human primates (cynomolgus and rhesus), dog, rat, and mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Capmatinib plasma concentrations were determined by using a validated LC-MS/MS assay, which has been described elsewhere. 35 The assay used a lower limit of quantitation of ˜1 ng/mL using 100 μL of plasma sample in di-potassium EDTA. Sample preparation in 96-well plates comprised addition of a 100 μL aliquot of the samples, a 50 μL aliquot of the internal standard working solution, and a 300 μL aliquot of 0.5% ammonium hydroxide solution to the designated wells.…”
Section: Pk Assessmentsmentioning
confidence: 99%
“…34 In an absorption, distribution, metabolism, and excretion study in healthy male volunteers, 14 Clabeled capmatinib (a single 600 mg oral dose, capsule formulation) had substantial systemic availability, was extensively metabolized, and was mainly distributed to the peripheral tissue, with a mean elimination t 1/2 of 7.84 hours. 35 The highest tested dose of capmatinib in tablet formulation reported in the literature is 400 mg BID, 13 , 32 , 36 and all published pharmacokinetic (PK) studies have been conducted under fasted conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The perturbation of the HGF/MET signaling by the inhibition of MET could disrupt the permeability balance in the vascular endothelium [ 36 ], thus, promoting edema development. A study in healthy volunteers treated with capmatinib showed that the drug was largely distributed to the peripheral tissues [ 37 ], which could contribute to the development of peripheral edema in patients treated with MET inhibitors.…”
Section: Potential Mechanisms Of Edema With Met Inhibitorsmentioning
confidence: 99%